Heavy Fermion Superconductivity and Antiferromagnetic Ordering in CePt3Si without Inversion Symmetry - Bauer, E.; Kaldarar, H.; Prokofiev, A.; Royanian, E.; Amato, A.; Sereni, J.G.; Bramer-Escamilla, W.; Bonalde, I.; Sereni, Julián (The Physical Society of Japan, 2007)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Laboratorio de Bajas Temperaturas; Argentina